1990
DOI: 10.1007/bf01912085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of kinetic data by Johnson-Mehl equation

Abstract: Johnson-Mehl equation is written as da.~. = kn tn_ 1 (1 -a ) where a is the degree of reaction, t time and n a constant. Use of this equation in kinetic analysis present problems because of the presence of a 't' term on the right hand side. The equation is not a true -kinetic equation and k is not a true rate constant.This paper presents a brief discussion on the use of this equation as such or in a modified form and also indicates the proper procedure for evaluating kinetic parameters correctly. Some experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…When f 1, during the early stages of recrystallization, this expression provides a good approximation to experiment; however, once the plateau region is reached at the later stages of recrystallization the formation rate slows and one must turn to the Kolmogorov-Johnson-Mehl-Avrami (KJMA) equation [426][427][428][429][430][431][432]:…”
Section: Crystallization and Recrystallizationmentioning
confidence: 99%
“…When f 1, during the early stages of recrystallization, this expression provides a good approximation to experiment; however, once the plateau region is reached at the later stages of recrystallization the formation rate slows and one must turn to the Kolmogorov-Johnson-Mehl-Avrami (KJMA) equation [426][427][428][429][430][431][432]:…”
Section: Crystallization and Recrystallizationmentioning
confidence: 99%
“…In order to develop the model that predicts the air-oxidation breakaway timing, literature regarding the phase transformation from tetragonal to monoclinic ZrO 2 were investigated. Tsubakino et al reported the relationship between the phase transformation (tetragonal to monoclinic) time and temperature using the Johnson-Mehl equation (Equation ( 2)) [21,22], which describes the time-transformation isotherms in alloy systems [23].…”
Section: Development Of the Improved Air-oxidation Breakaway Modelmentioning
confidence: 99%
“…In a recent paper [6] Sarkar and Ray have suggested that this equation is not a true kinetic equation on the premise that it cannot be expressed in the form of a standard kinetic equation (2) where K(T) is the rate constant and f(a) is a function of a. (15) of [6]) the authors used for kinetic plots in their paper. (1) after suitable manipulation can be expressed in a form given by Eq.…”
mentioning
confidence: 99%
“…This is not so since Eq. 7 of [6]) the authors claim that the gradient is given by -a/(1-a), a term that increases monotonously. This is the equation (Eq.…”
mentioning
confidence: 99%